Magnetotelluric constraints on natural hydrogen potential in the southern Gawler Craton, Australia - R. Margiono; R. Daruso; A. Gubina; G. Heinson; S. Constable; B. Kay; G. Boren (Australian Journal of Earth Sciences, 2026)

First detection and tracing of grapevine red blotch virus (GRBV) in Australia using tiled amplicon sequencing - Tonny Kinene; Andrew S. Taylor; Richard Fennessy; Brenda A. Coutts; David Lovelock; Cuiping Wang; Kamalpreet Kaur; Thao Tran; Brendan Rodoni; Fiona E. Constable; Monica A. Kehoe (Archives of Virology, 2025)
Grapevine red blotch virus (GRBV; species Grablovirus vitis , genus Grablovirus , family Geminiviridae ) poses a significant threat to viticulture worldwide, impacting grapevine health and wine quality. Here, we report the first detection and tracing of GRBV in Australia and provide a summary of a subsequent survey to determine the extent of GRBV distribution in Western Australia. Additionally, the study introduces a tiled amplicon sequencing method, which, when combined with long-read nanopore sequencing, enables rapid GRBV genome sequencing. Our analysis suggests a single introduction of GRBV from North America to Australia through the state of Victoria and subsequently to Western Australia. Finally, this study provides insight into the epidemiology of GRBV, based on strain variation and distribution, which is a crucial step in supporting an emergency biosecurity response and implementing effective control measures to safeguard the sustainability of the wine industry in Australia.

First report of watermelon crinkle leaf associated virus-1 (WCLaV-1) in watermelon (Citrullus lanatus) in Australia - S. Mulholland; O. Wildman; W. M. Kinoti; F. Constable; A. Daly; L. Tesoriero; S. Maina; T. A. Chapman (Journal of Plant Pathology, 2022)
Surveys of key cucurbit production regions in New South Wales, Australia were undertaken to catalogue the diversity of viral pathogens affecting field grown cropping systems. Analysis of the collected isolates confirmed a detection of watermelon crinkle leaf associated virus-1 (WCLaV-1) in watermelon constituting the first report of WCLaV-1 in Australia. A mixed infection of WCLaV-1 and watermelon mosaic virus (WMV) was also detected constituting the first report of this type of pathogen combination.

Responses of Southern Ocean Seafloor Habitats and Communities to Global and Local Drivers of Change - Madeleine J. Brasier; David Barnes; Narissa Bax; Angelika Brandt; Anne B. Christianson; Andrew J. Constable; Rachel Downey; Blanca Figuerola; Huw Griffiths; Julian Gutt; Susanne Lockhart; Simon A. Morley; et al. (Frontiers in Marine Science, 2021)
Knowledge of life on the Southern Ocean seafloor has substantially grown since the beginning of this century with increasing ship-based surveys and regular monitoring sites, new technologies and greatly enhanced data sharing. However, seafloor habitats and their communities exhibit high spatial variability and heterogeneity that challenges the way in which we assess the state of the Southern Ocean benthos on larger scales. The Antarctic shelf is rich in diversity compared with deeper water areas, important for storing carbon (“blue carbon”) and provides habitat for commercial fish species. In this paper, we focus on the seafloor habitats of the Antarctic shelf, which are vulnerable to drivers of change including increasing ocean temperatures, iceberg scour, sea ice melt, ocean acidification, fishing pressures, pollution and non-indigenous species. Some of the most vulnerable areas include the West Antarctic Peninsula, which is experiencing rapid regional warming and increased iceberg-scouring, subantarctic islands and tourist destinations where human activities and environmental conditions increase the potential for the establishment of non-indigenous species and active fishing areas around South Georgia, Heard and MacDonald Islands. Vulnerable species include those in areas of regional warming with low thermal tolerance, calcifying species susceptible to increasing ocean acidity as well as slow-growing habitat-forming species that can be damaged by fishing gears e.g., sponges, bryozoan, and coral species. Management regimes can protect seafloor habitats and key species from fishing activities; some areas will need more protection than others, accounting for specific traits that make species vulnerable, slow growing and long-lived species, restricted locations with optimum physiological conditions and available food, and restricted distributions of rare species. Ecosystem-based management practices and long-term, highly protected areas may be the most effective tools in the preservation of vulnerable seafloor habitats. Here, we focus on outlining seafloor responses to drivers of change observed to date and projections for the future. We discuss the need for action to preserve seafloor habitats under climate change, fishing pressures and other anthropogenic impacts.

Combating ecosystem collapse from the tropics to the Antarctic - Dana M. Bergstrom; Barbara C. Wienecke; John van den Hoff; Lesley Hughes; David B. Lindenmayer; Tracy D. Ainsworth; Christopher M. Baker; Lucie Bland; David M. J. S. Bowman; Shaun T. Brooks; Josep G. Canadell; Andrew J. Constable; et al. (Global Change Biology, 2021)
Globally, collapse of ecosystems—potentially irreversible change to ecosystem structure, composition and function—imperils biodiversity, human health and well‐being. We examine the current state and recent trajectories of 19 ecosystems, spanning 58° of latitude across 7.7 M km 2 , from Australia's coral reefs to terrestrial Antarctica. Pressures from global climate change and regional human impacts, occurring as chronic ‘presses’ and/or acute ‘pulses’, drive ecosystem collapse. Ecosystem responses to 5–17 pressures were categorised as four collapse profiles—abrupt, smooth, stepped and fluctuating. The manifestation of widespread ecosystem collapse is a stark warning of the necessity to take action. We present a three‐step assessment and management framework (3As Pathway Awareness , Anticipation and Action ) to aid strategic and effective mitigation to alleviate further degradation to help secure our future.

Effect of self-generation for initial selection on breeding better cotton - S. M. Liu; G. A. Constable (Euphytica, 2017)

Benefit of spatial analysis for furrow irrigated cotton breeding trials - S. M. Liu; G. A. Constable; B. R. Cullis; W. N. Stiller; P. E. Reid (Euphytica, 2015)

Climate change and Southern Ocean ecosystems I: how changes in physical habitats directly affect marine biota - Andrew J. Constable; Jessica Melbourne‐Thomas; Stuart P. Corney; Kevin R. Arrigo; Christophe Barbraud; David K. A. Barnes; Nathaniel L. Bindoff; Philip W. Boyd; Angelika Brandt; Daniel P. Costa; Andrew T. Davidson; Hugh W. Ducklow; et al. (Global Change Biology, 2014)
Antarctic and Southern Ocean ( ASO ) marine ecosystems have been changing for at least the last 30 years, including in response to increasing ocean temperatures and changes in the extent and seasonality of sea ice; the magnitude and direction of these changes differ between regions around Antarctica that could see populations of the same species changing differently in different regions. This article reviews current and expected changes in ASO physical habitats in response to climate change. It then reviews how these changes may impact the autecology of marine biota of this polar region: microbes, zooplankton, salps, Antarctic krill, fish, cephalopods, marine mammals, seabirds, and benthos. The general prognosis for ASO marine habitats is for an overall warming and freshening, strengthening of westerly winds, with a potential pole‐ward movement of those winds and the frontal systems, and an increase in ocean eddy activity. Many habitat parameters will have regionally specific changes, particularly relating to sea ice characteristics and seasonal dynamics. Lower trophic levels are expected to move south as the ocean conditions in which they are currently found move pole‐ward. For Antarctic krill and finfish, the latitudinal breadth of their range will depend on their tolerance of warming oceans and changes to productivity. Ocean acidification is a concern not only for calcifying organisms but also for crustaceans such as Antarctic krill; it is also likely to be the most important change in benthic habitats over the coming century. For marine mammals and birds, the expected changes primarily relate to their flexibility in moving to alternative locations for food and the energetic cost of longer or more complex foraging trips for those that are bound to breeding colonies. Few species are sufficiently well studied to make comprehensive species‐specific vulnerability assessments possible. Priorities for future work are discussed.

Diffusion and mobility of electrically conducting defects in olivine - S. Constable; A. Duba (Physics and Chemistry of Minerals, 2002)

Modelling changes in VOC emission in response to climate change in the continental United States - JohN. V. H . Constable; AleX. B. Guenther; David S. Schimel; Russell K. Monson (Global Change Biology, 1999)
Summary The alteration of climate is driven not only by anthropogenic activities, but also by biosphere processes that change in conjunction with climate. Emission of volatile organic compounds (VOCs) from vegetation may be particularly sensitive to changes in climate and may play an important role in climate forcing through their influence on the atmospheric oxidative balance, greenhouse gas concentration, and the formation of aerosols. Using the VEMAP vegetation database and associated vegetation responses to climate change, this study examined the independent and combined effects of simulated changes in temperature, CO 2 concentration, and vegetation distribution on annual emissions of isoprene, monoterpenes, and other reactive VOCs (ORVOCs) from potential vegetation of the continental United States. Temperature effects were modelled according to the direct influence of temperature on enzymatic isoprene production and the vapour pressure of monoterpenes and ORVOCs. The effect of elevated CO 2 concentration was modelled according to increases in foliar biomass per unit of emitting surface area. The effects of vegetation distribution reflects simulated changes in species spatial distribution and areal coverage by 21 different vegetation classes. Simulated climate warming associated with a doubled atmospheric CO 2 concentration enhanced total modelled VOC emission by 81.8% (isoprene + 82.1%, monoterpenes + 81.6%, ORVOC + 81.1%), whereas a simulated doubled CO 2 alone enhanced total modelled VOC emission by only + 11.8% (isoprene + 13.7%, monoterpenes + 4.1%, ORVOC + 11.7%). A simulated redistribution of vegetation in response to altered temperatures and precipitation patterns caused total modelled VOC emission to decline by 10.4% (isoprene – 11.7%, monoterpenes – 18.6%, ORVOC 0.0%) driven by a decline in area covered by vegetation classes emitting VOCs at high rates. Thus, the positive effect of leaf‐level adjustments to elevated CO 2 (i.e. increases in foliar biomass) is balanced by the negative effect of ecosystem‐level adjustments to climate (i.e. decreases in areal coverage of species emitting VOC at high rates).